The Effect Of Transfer Pricing, Political Connection, Leverage, And Deferred Tax On Tax Avoidance - Ayu Budi Sayati; Einde Evana; Fitra Dharma (Cita konsultindo, 2023)
Tax is the largest income for a country, the tax itself under the law is coercive, which means that taxpayers must pay taxes from their income if they have reached the required taxable limit. But in reality there are still many taxpayers who deliberately avoid paying taxes influenced by factors that can affect tax evasion. This study analyzes the factors of transfer pricing, political connections, leverage and deferred taxes on tax avoidance using multiple regression analysis of manufacturing companies listed on the IDX for the 2019-2021 period. This study found that transfer pricing and leverage have a significant effect on tax evasion, while political connections and deferred tax variables have no significant effect.